World Economic and Social Survey 2014/2015 - United Nations (United Nations, 2016)
The year 2015 was one of global action concerning the Millennium Development Goals (MDGs) and other challenges. The 2030 Agenda for Sustainable Development along with a set of new Sustainable Development Goals (SDGs) will apply universally to all countries. As the MDG experience shows, setting ambitious goals is the first step; achieving them requires concrete actions. This publication reviews economic, social and environmental policies implemented at the national level and the institutional aspects that enabled them, bringing about significant progress towards achieving the MDGs. The Survey draws a set of policy lessons that States will find helpful in formulating strategies and policies for implementing the 2030 Agenda.